(untitled) (Research, Society and Development, 2021)
Several axonal growth inhibitors have already been identified following spinal cord injury, the most known being myelin-derived proteins, such as Nogo-A. The present study aimed to correlate the formation of glial scar with the beginning of growth inhibitor, Nogo-A, release in rats previously submitted to compressive spinal cord injury. For this, 12 male and female Wistar rats (250 ± 50g) were divided into 3 groups of 4 animals each, according to the animals’ euthanasia time after spinal cord injury (G3 - three days; G5 - five days; G7 - seven days). Spinal cord injuries were induced by means of dorsal laminectomy of the T10 vertebra and epidural compression. Histopathological evaluation and immunoreactivity of the Nogo-A axonal growth inhibitor were performed. It was observed that there was the release of the axonal inhibitor Nogo-A after 24h after the occurrence of spinal cord injury, and that the glial scar must be maintained, in this time interval, in order to guarantee the rebalancing of the post-trauma environment. Thus, it is suggested that the glial scar should be maintained in the acute phase of the lesion, guaranteeing its numerous benefits for the rebalancing of the post-injured environment and, after 24 hours, when the release of the studied axonal growth inhibitor begins, it should be removed.